Analisis pelaksanaan manajemen berbasis sekolah bidang peserta didik berdasarkan 3 pilar MBS di sekolah dasar - Febriana Hendra Watik; Siti Wahyuningsih; Suharno Suharno (Didaktika Dwija Indria, 2021)
This study aims to analyze the implementation of school-based management (SBM), particularly in the areas of students based on the 3 pillars of SBM, such as school management, PAIKEM, and community participation. This research uses a qualitative case study approach. Data collection techniques used observation, interviews, questionnaires, and document analysis. The data validity used method and source triangulation techniques. Data analysis using theme analysis techniques. The results showed that SD Negeri Kusumodilagan had implemented the 3 pillars of School Based Management (MBS) well. The school is able to carry out school management, especially in the field of students by involving the cooperation of related parties. All teachers have implemented PAIKEM at SD Negeri Kusumodilagan by utilizing existing resources. In addition, community participation has increased compared to the previous academic year. Parents, school committees, DUDI, and the Health Office provide mutual support for the smooth running of the program of activities held by the school.